2014
DOI: 10.1186/1878-5085-5-1
|View full text |Cite
|
Sign up to set email alerts
|

Development of biomarker panel to predict, prevent and create treatments tailored to the persons with human papillomavirus-induced cervical precancerous lesions

Abstract: IntroductionHuman papillomavirus (HPV) induce many cancer conditions and cause cervical cancer, second in frequency of malignant disease in women.The aim was to develop biomarker panel for HPV-induced cervical precancerous diseases in patients infected with herpes simplex virus (HSV).Material and methodsThe study involved 71 women with cervical precancerous diseases (mean age 26 ± 5 years) revealed by colposcopic, cytomorphological, and ultrasound signs which were assessed according to the following: first gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 84 publications
(148 reference statements)
1
13
0
1
Order By: Relevance
“…There were illustrated extensive interrelations among virus action, cellular oxidative stress, gene damage, multiple immune pathways and proteomic changes in diabetes mellitus, cancer and many chronic disorders development; many of them are also related to HPV infection [96,97]. On the other hand, the obesity may induce the T cell response in virus infection [98].…”
Section: Discussionmentioning
confidence: 99%
“…There were illustrated extensive interrelations among virus action, cellular oxidative stress, gene damage, multiple immune pathways and proteomic changes in diabetes mellitus, cancer and many chronic disorders development; many of them are also related to HPV infection [96,97]. On the other hand, the obesity may induce the T cell response in virus infection [98].…”
Section: Discussionmentioning
confidence: 99%
“…Treg cytokine profile showed progressive increase with progressing disease indicating a poor cell mediated immunity with high grade lesions. Lazarenko et al (2014) have recently evaluated a panel of biomarkers for assessment of progression from healthy cervices to HPV infected, CIN and cancer. These included several cytokines (PBMC), HPV status, HSV antibodies, and newer biophysical techniques like cervical sonocervicography using ultrasonography which has shown a high specificity, sensitivity, positive predictive value and negative predictive value.…”
Section: Il-17mentioning
confidence: 99%
“…However biopsy is an invasive procedure and is particularly non-desirable in the younger women desirous of conserving menstrual and childbearing functions. Hence further studies were carried out by authors who have observed that the higher local or circulatory peripheral concentrations of some cytokines are indicative of a higher risk of progression from CIN 1 to CIN 2 or 3 and further to invasive cancer and metastasis (Adam et al, 1999;Fugimoto et al, 2000;Pardo-Govea et al, 2005;Bais et al, 2007;Sharma et al, 2007;Hong et al, 2010;Kemp et al, 2010;Ali et al, 2012;Mhatre et al, 2012;Peghini et al, 2012;Lazarenko et al, 2014). Souza et al (2013) recently demonstrated higher serum concentrations of IL-17, mean-pg/ml: 22.50 in HSIL vs 12.20 in LSIL, and of IL-22, mean pg/ml 168.2 vs 61.48, p<0.05 respectively.…”
Section: Cytokines As Markers Of High Risk Of Progression Of Cin Gradesmentioning
confidence: 99%
“…Of these, 25 [86, were not reviewed further because they were a republication or reanalysis of data that were already used to evaluate the health claim and/or because they had scientific deficiencies that prevented FDA from drawing scientific conclusions from the study (Table 1). For example, studies that measured biomarkers that had not been previously validated for the specific cancer under study (e.g., serum level of insulin-like growth factor and cervical dysplasia) [110,111] were excluded because they did not provide reliable evidence for risk reduction, and therefore, no scientific conclusions could be drawn from them for the evaluation of a qualified health claim about cancer. Studies for which no information was provided about the validation of the food frequency questionnaire used were also excluded because failure to validate a food-frequency questionnaire may lead to false conclusions about associations between dietary factors and disease risk [112,113].…”
Section: Tomatoes and Cancer Risk Reductionmentioning
confidence: 99%